The transcervical approach for parapharyngeal space pleomorphic adenomas: indications and technique. - Gilad Horowitz; Oded Ben-Ari; Oshri Wasserzug; Noam Weizman; Moshe Yehuda; Dan M Fliss (PLoS ONE)
Background Head and Neck Parapharyngeal space tumors are rare. Pleomorphic Adenomas are the most common Parapharyngeal space tumors. The purpose of this study was to define preoperative criteria for enabling full extirpation of parapharyngeal space pleomorphic adenomas via the transcervical approach while minimizing functional and cosmetic morbidity. Methods The surgical records and medical charts of 19 females and 10 males with parapharyngeal space pleomorphic adenomas operated between 1993 and 2012 were reviewed. Results Fifteen patients were operated by a simple transcervical approach, 13 by a transparotid transcervical approach, and one by a transmandibular transcervical approach. Complications included facial nerve paralysis, infection, hemorrhage and first bite syndrome. There were three recurrences, but neither recurrence nor complications were associated with the type of surgical approach. Conclusion A simple transcervical approach is preferred for parapharyngeal space pleomorphic adenomas with narrow attachments to the deep lobe of the parotid gland and for pleomorphic adenomas originating in a minor salivary gland within the parapharyngeal space.